Rasionalitas: Overview terhadap Pemikiran dalam 50 Tahun Terakhir - Rahmat Hidayat (Faculty of Psychology Universitas Gadjah Mada, 2016)
Humans are often viewed as rational beings. Studies on behavioral economics regarding rationality depend on both economic theories of rational decision making, as well as psychological cognitive theories behind mental and behavioral processes. Experimental research over the last half century has shown systematic deviations from the principle of rationality, also called anomaly, in individual judgment and decision-making. The theoretical explanation for the anomaly currently emphasizes on the limitations of individual rationality. Furthermore, limitations in rationality are seen as a universal feature of the individual. However, in recent times, there have been studies that attempt to prove individual differences as a factor behind anomalies in judgment and decision making. This paper attempts to summarize both points of view, and discusses the need to develop an instrument to measure rationality as an individual discriminatory factor in judgment and decision making.